Pandemics and Heritage: understanding the impact of the Covid-19 pandemic on Archaeotourism in South Africa - Eswaran, Nithya (University of the Witwatersrand, Johannesburg, 2023)
The project explores the impact of the Covid-19 pandemic on archaeotourism at three public visitation sites in South Africa. According to the 2021 UNESCO report on the impact of Covid- 19 on heritage tourism, visitors to Africa decreased by 71% in 2020. The drop significantly impacted the revenue of the continent (UNESCO 2021). This research focuses on assessing the effects of the COVID-19 pandemic locally by examining two UNESCO World Heritage sites: the Sterkfontein Caves in the Cradle of Humankind, Gauteng Province, and Main Caves in Giant’s Castle Game Reserve, KwaZulu-Natal Province. The third study site is the Origins Centre Museum at the University of Witwatersrand in Johannesburg. These sites are open to tourists for guided tours. Quantitative data from Kruger National Park is collated to analyse the pandemic's influence on public, nature-based sites for comparison to culture sites
A research report submitted in partial fulfillment of the requirements for the degree of Master of MSc, Archaeology, to the Faculty of Science, School of School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2023
Keywords: Pandemics and Heritage; Covid-19 pandemic; Archaeotourism; South Africa; UCTD; SDG-3: Good health and well-being